2020
DOI: 10.1021/acs.iecr.9b06639
|View full text |Cite
|
Sign up to set email alerts
|

Prussian Blue Decoration on Polyacrylonitrile Nanofibers Using Polydopamine for Effective Cs Ion Removal

Abstract: We prepared Prussian blue (PB) nanoparticles immobilized on the surface of nanofibers to adsorb the Cs ions effectively. The nanofibers were fabricated by electrospinning of polyacrylonitrile (PAN), and polydopamine (PD) was polymerized to immobilize PB on the surfaces of the nanofibers. PD is known to adhere easily on any substrate, and it could coat the surface of the PAN nanofibers. The catechol groups in PD could also bind to Fe­(III) and Fe­(II) ions, and subsequently, the Fe ions reacted further to form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 44 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…The adsorbents were also incorporated into a crosslinked, bead-type copolymer resin composed of polystyrene (PS) and divinylbenzene (DVB) [ 30 ]. PB has also been immobilized by means of a linkage of polydopamine (PD) on the surface of nanofibers fabricated by electrospinning of polyacrylonitrile (PAN) [ 31 ], on poly(vinyl alcohol) (PVA) sponge [ 32 , 33 ], caged in a gel of sodium alginate [ 34 ], in the same colloid to develop an intestinal release delivery system [ 35 ], in spongiform adsorbents [ 36 ], bonded to sepiolite (hydrated magnesium silicate) [ 37 ], embedded into a binder matrix [ 38 ], in porous cellulose aerogel [ 39 ] or in microporous carboxymethyl cellulose nanofibrils membranes [ 40 ]. Hayashi et al found that PB/PBA precipitated spontaneously in agarose gels, and these materials were able to adsorb Cs + ions effectively [ 41 ].…”
Section: Adsorption Properties Of Pbmentioning
confidence: 99%
“…The adsorbents were also incorporated into a crosslinked, bead-type copolymer resin composed of polystyrene (PS) and divinylbenzene (DVB) [ 30 ]. PB has also been immobilized by means of a linkage of polydopamine (PD) on the surface of nanofibers fabricated by electrospinning of polyacrylonitrile (PAN) [ 31 ], on poly(vinyl alcohol) (PVA) sponge [ 32 , 33 ], caged in a gel of sodium alginate [ 34 ], in the same colloid to develop an intestinal release delivery system [ 35 ], in spongiform adsorbents [ 36 ], bonded to sepiolite (hydrated magnesium silicate) [ 37 ], embedded into a binder matrix [ 38 ], in porous cellulose aerogel [ 39 ] or in microporous carboxymethyl cellulose nanofibrils membranes [ 40 ]. Hayashi et al found that PB/PBA precipitated spontaneously in agarose gels, and these materials were able to adsorb Cs + ions effectively [ 41 ].…”
Section: Adsorption Properties Of Pbmentioning
confidence: 99%
“…However, nuclear power produces about 2000 to 2300 metric tons of radionuclide waste into the environment while providing electricity. , Once the highly radioactive wastewater flows into the ocean, it will cause serious contamination of soil and water with radionuclides. Radionuclide waste contains cesium, strontium, cobalt, tritium, lanthanide elements, actinide elements, and so forth. Radioactive cesium ( 137 Cs) is one of the most dangerous species with a high fission yield (6.09%), long half-life (30.2 years), high-energy gamma radiation, high solubility, volatility, and activity in water, and has the ability to form compounds or complexes with many other substances in urban and rural areas. , Because Cs ions have biological properties similar to K ions and Na ions, they can enter the body and cause serious health problems. In order to solve these problems, effective removal of low radioactive Cs ions from nuclear wastewater is an urgent need. Up to now, adsorption has been widely regarded as a preferred method to remove Cs ions from wastewater due to the advantages of feasibility, high efficiency, and low cost. In recent years, various adsorbents including mesoporous silicon, porous organic polymers, metal–organic frameworks, , graphene metal oxides, and other functional materials have been developed for the adsorptive removal of Cs + .…”
Section: Introductionmentioning
confidence: 99%
“…1 depicts the steps involved in creating the self-propelling Tube-D-PB shuttle. The dopamine coating was used because of its high adhesive property, 10 which enabled the strong binding to both PB and the tube surface. Dopamine was successfully coated onto the raw tube surface, as confirmed visually by a change in the tube opacity from transparent to opaque (Fig.…”
mentioning
confidence: 99%